2018
DOI: 10.24293/ijcpml.v23i1.1191
|View full text |Cite
|
Sign up to set email alerts
|

ANTIBIOGRAM (Antibiogram)

Abstract: Resistensi antibiotika telah menjadi masalah kesehatan global. Upaya yang dilakukan untuk mengatasi kegentingan resistensiantibiotika adalah melalui penggunaan antibiotika secara bijak. Salah satu strategi penggunaan antibiotika secara bijak adalah denganmenyusun dan menggunakan antibiogram. Antibiogram menuntun peklinik dalam memilih pengobatan antibiotika empiris terbaiksementara menunggu hasil kultur dan uji kepekaan antibiotika. Antibiogram dapat dijadikan dasar dalam penyusunan pedomanpengobatan antibioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In hospitals and clinical settings, multidrug-resistant infections lead to prolonged hospitalization, increased rates of morbidity/mortality, and overall healthcare sector costs (Revelas, 2012). Antibiotic susceptibility testing of microorganisms (via antibiograms) should be carried out at least once a year and serve as a basis for updating hospital empiric antibiotic policies (Akualing and Sri Rejeki, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In hospitals and clinical settings, multidrug-resistant infections lead to prolonged hospitalization, increased rates of morbidity/mortality, and overall healthcare sector costs (Revelas, 2012). Antibiotic susceptibility testing of microorganisms (via antibiograms) should be carried out at least once a year and serve as a basis for updating hospital empiric antibiotic policies (Akualing and Sri Rejeki, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This report shows the alarming spread of antibiotic resistance worldwide [3]. A research conducted in Indonesia showed that of 781 patients in the hospital, 81% of them had resistance with ampicillin, 73% resistance with cotrimoxazole and 56% resist against Escherichia coli [4]. This study was supported by research conducted by Huda in 2016, it was confirmed that Escherichia coli was the most resistant to Sulfamethoxazole (100%), Ampicillin (93.3%) and Cefadroxil (90.9%) [5] and another study conducted by Kibret in 2011 at northeast Ethiopia found that high levels of resistance to erythromycin (89.4%), amoxicillin (86.0%) [6].…”
Section: Introductionmentioning
confidence: 88%
“…Similarly, the percentage of resistance was obtained by dividing ∑R by n. The more isolates tested (the more n), the more accurate the percent sensitivity and the percent resistance. Percent sensitivity on the antibiogram is color-coded and numbered if the number is close to 100 or even 100, the antibiotic is sensitive and recommended for further treatment (Akualing & Rejeki, 2018).…”
Section: Methodsmentioning
confidence: 99%